Exploring the motivational challenges of special needs students in learning specific vocational skills subjects through self-determination theory approach - Mustapa, Ayu Ashilla; Mohd Sufian Kang, Enio Kang (Human Resources Management Academic Research Society (HRMARS), 2024)
Teaching of specific vocational skills subject (KVS) for special need students (MBK) in secondary schools enhances the students’ skills and knowledge pertaining to specific jobs. In the following section, this research employs Self-Determination Theory to analyse MBK’s motivating barriers in studying KVS subjects. The theory of SDT applied here in gives a preview of MBK’s motivational setup in relation to the KVS learning and understanding the key aspects that determine MBK motivation. SDT involves satisfaction of basic psychological needs, that is autonomy, competence and connectivity as important to intrinsic motivation and learning. This paper also outlines possible improvement and interventions that may help increase their motivation as well as performance in these subjects. The finding of this concept paper should inform the advancement of the reviewed education framework and offer helpful insights to educators and policy makers in the enhancement of special needs student needs to motivate and achieve in vocational skills subjects.